Seasonal effect on the prevalence of virulence genes of non-O157 Verotoxic E.coli serogroups in faeces of cattle calves - PARUL; BIST, B; SHARMA, B; KUMAR, A; SINGH, S P; JAIN, U; GOSWAMI, M; MISHRA, R P; BASAK, G (The Indian Journal of Animal Sciences, 2023)
Calves faecal samples (n=216) were investigated to observe the effect of seasons on the prevalence of serogroups and virulence genes of non-O157 VTEC. A total of 177 (81.94%) E. coli were isolated and 32 (14.81%) were identified as VTEC and serotyping resulted in 13 different non-O157 ‘O’ serogroups. The prevalence of serogroups and their virulence genes was found to be influenced by seasons and highest number were shed in summer (22.22%) followed by rainy (13.88%) and winter season (8.33%), respectively. A higher prevalence of O9 and O11 serogroups (25% each) was observed in summers. Molecular detection of virulence genes revealed the overall prevalence of vt1 to be 37.5%, vt2 43.8%, (vt1+vt2) 18.8%, eaeA 21.9% and hlyA 34.4% genes. Dominance of hlyA 50% was observed in summers, whereas vt1 and vt2 were more prevalent during rain (50% each). The study revealed the link between the occurrence of hlyA gene and O9, O11 serogroups in summers as both the serogroups were hlyA gene bearer. This association might be responsible for more VTEC outbreaks in summers. So, faecal contamination of raw milk seems to pose greater threat of non-O157 VTEC outbreak during hotter and humid months.